Developments in the Recycling of Wood and Wood Fibre in the UK: A Review - Morwenna J. Spear; Athanasios Dimitriou; Simon F. Curling; Graham A. Ormondroyd (Fibers, 2025)
There is great interest in using bio-based materials to reduce the climate impact of materials. Similarly, there is an increased focus on the circular economy and recycling of materials to increase material efficiency and reduce waste. In the case of wood waste, this provides a cluster of benefits but has led to a high demand for the reclaimed material. This review provides updates on several technologies where wood fibre recycling and products from recycled wood fibre are breaking into new markets, including wood fibre insulation products, wood plastic composites, oriented strand boards, and fibreboards. Emerging technologies, such as the ability to recycle medium-density fibreboards, in addition to the more commonly recycled solid wood or particleboard, will allow for a new set of options within the wood cascading chain. Looking ahead, there are likely to be advances in new composite products, as well as other feedstock materials derived from reclaimed wood, such as nanocellulose, pyrolysis oils, or wood polymers reclaimed from the wood feedstock. This review arose from an investigation into the wood recycling sector in the UK. So, the horizon scanning exercise presented here considers the needs and challenges that may arise, if the volume of recycled wood fibre can be increased, in an already highly active market. Such developments would permit an increase in the manufacture of new-generation long-service-life products to enhance carbon storage, and potentially a shift away from bioenergy generation.